2023
DOI: 10.3389/fpsyg.2022.1020963
|View full text |Cite
|
Sign up to set email alerts
|

Children’s social emotional competence in Pakistan and Sweden: Factor structure and measurement invariance of the Social Competence Scale (teacher edition)

Abstract: IntroductionSocial emotional competence is fundamental to the positive development of children and youth. Accurately understanding and assessing children’s social emotional competencies, using psychometrically sound instruments, are essential to global efforts to support children’s social emotional learning, academic achievements, and health. This study examined the psychometric properties of a teacher-reported measure of young children’s social emotional competence, the Social Competence Scale – Teacher editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The Corona outbreak has engendered a growing amount of scholarly research that explores the correlation between social–emotional competence and psychological wellness ( 29 ). A research study determined that children possessing elevated levels of social–emotional competence demonstrated less occurrence of cognitive and behavioral difficulties ( 30 , 31 ). Correspondingly, additional evidence emerged affirming that heightened social–emotional competence aids individuals in enhancing their self-efficacy, job satisfaction, and psychological wellness.…”
Section: Introductionmentioning
confidence: 99%
“…The Corona outbreak has engendered a growing amount of scholarly research that explores the correlation between social–emotional competence and psychological wellness ( 29 ). A research study determined that children possessing elevated levels of social–emotional competence demonstrated less occurrence of cognitive and behavioral difficulties ( 30 , 31 ). Correspondingly, additional evidence emerged affirming that heightened social–emotional competence aids individuals in enhancing their self-efficacy, job satisfaction, and psychological wellness.…”
Section: Introductionmentioning
confidence: 99%
“…At the core of these cultural values lie positive emotions, representing the universal human desire for happiness, fulfillment, and well-being. A qualitative survey was conducted to identify the positive emotions and culture-specific values in school children (Thomas, et al, 2023). The study aimed to see the expression and representation of positive emotions and values.…”
Section: Introductionmentioning
confidence: 99%
“…The study aimed to see the expression and representation of positive emotions and values. The study revealed that children's social emotional competence is fundamental to their positive development, and cultural norms and values play a crucial role in shaping their emotional and behavioral development (Thomas, et al, 2023;Waheed et al, 2022).…”
Section: Introductionmentioning
confidence: 99%